The first resolved imaging of milliarcsecond-scale jets in Circinus X-1 - Miller-Jones, James; Moin, Aquib; Tingay, Steven; Reynolds, Cormac; Phillips, C.; Tzioumis, A.; Fender, R.; McCallum, J.; Nicolson, G.; Tudose, V. (Wiley-Blackwell Publishing Ltd., 2012)
We present the first resolved imaging of the milliarcsecond-scale jets in the neutron star X-ray binary Circinus X-1, made using the Australian Long Baseline Array. The angular extent of the resolved jets is ~20 mas, corresponding to a physical scale of ~150 au at the assumed distance of 7.8 kpc. The jet position angle is relatively consistent with previous arcsecond-scale imaging with the Australia Telescope Compact Array. The radio emission is symmetric about the peak, and is unresolved along the minor axis, constraining the opening angle to be <20°. We observe evidence for outward motion of the components between the two halves of the observation. Constraints on the proper motion of the radio-emitting components suggest that they are only mildly relativistic, although we cannot definitively rule out the presence of the unseen, ultrarelativistic (G > 15) flow previously inferred to exist in this system.